2018
DOI: 10.21037/jgo.2017.06.09
|View full text |Cite
|
Sign up to set email alerts
|

How does the tumor microenvironment play a role in hepatobiliary tumors?

Abstract: The tumor microenvironment (TME) is defined as the structural and dynamic network of cellular and non-cellular interactions between malignant cells and the surrounding non-malignant matrix. Hepatocellular carcinoma (HCC) and pancreatic ductal adenocarcinoma (PDAC) are two of the most challenging gastrointestinal malignancies. Despite clinical advancements in understanding tumor biology and growth of the chemotherapeutic industry, there have been no corresponding improvements in prognosis and overall survival o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 106 publications
2
19
0
Order By: Relevance
“…Although the role of the tumor microenvironment in tumor progression is well established (Amicone and Marchetti, ; Kamil and Rowe, ), the cross‐talk between HSC and HCC cells in liver cancer metastasis has hardly been explored. Our previous study showed that activated HSCs create an immunosuppressive microenvironment in an orthotopic liver tumor mouse model by inducing expansion of the Tregs and MDSCs (Zhao et al , ) (Zhao et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of the tumor microenvironment in tumor progression is well established (Amicone and Marchetti, ; Kamil and Rowe, ), the cross‐talk between HSC and HCC cells in liver cancer metastasis has hardly been explored. Our previous study showed that activated HSCs create an immunosuppressive microenvironment in an orthotopic liver tumor mouse model by inducing expansion of the Tregs and MDSCs (Zhao et al , ) (Zhao et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the tumor microenvironment (TME), multiple cell type such as immune cells, vascular endothelial cells, and fibroblasts collectively work to regulate tumorigenesis. Disorders of the TME increase the occurrence of tumor recurrence, metastasis, and chemoresistance 95 . TAMs are one of the major TME cells that provide an immunosuppressive milieu for tumor progression and secrete many growth factors that suppress the proinflammatory cytokine release in the TME.…”
Section: Pathological Roles Of Mφ-evs In Diseasementioning
confidence: 99%
“…The hepatic stromal cells include vascular endothelial cells, sinusoidal endothelial cells, stellate cells, adipose cells, liver progenitor cells, immune inflammatory cells and cancer-associated fibroblasts. The crosstalk between liver cancer cells and immune inflammatory cells as well as cancer-associated fibroblasts significantly influences tumor growth and metastasis [6][7][8][9]. It has also been documented that higher levels of activated hepatic stellate cells are associated to the increased portal vein invasion by up-regulation of integrins/FAK signaling pathway and MMP levels [10].…”
Section: Ivyspringmentioning
confidence: 99%